Rainier Vista and Music Pavilion, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Printed on image: Rainier Vista and Music Pavilion, Alaska Yukon Pacific Exposition, Seattle, Wash., 1909 (Official post card) Printed on verso: Portland Post Card Co. PH Coll 777 PPCC.143 (See also PH Coll 78.152) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number